P215 PROGNOSTIC IMPACT OF EARLY VERSUS DEFERRED CORONARY ANGIOGRAPHY IN MINOCA PATIENTS. (18th May 2022) - Armillotta, M; Sansonetti, A; Amicone, S; Stefanizzi, A; Fabrizio, M; Angeli, F; Bergamaschi, L; Paolisso, P; Impellizzeri, A; Foà, A; Rinaldi, A; Casella, G; et al.
Abstract: Background: Although an early invasive strategy (coronary angiography performed < 24 hours) is associated with a lower risk of recurrent/refractory ischaemia among patients with acute myocardial infarction (AMI) and obstructive coronary arteries, the optimal timing of invasive examination in patients with non–obstructive coronary arteries and non–ST–segment elevation presentation (NSTE–MINOCA) has not been explored. Purpose: This study tested the hypothesis that, compared to early (< 24 h) invasive strategy, deferred (≥ 24 h) coronary angiography has an equivalent prognostic impact in patients with NSTE–MINOCA. Methods: From 2016 to 2020, all consecutive MINOCA patients diagnosed according to the current ESC diagnostic criteria (angiographic conventional cut–off of < 50% coronary stenosis without a clinically apparent alternative diagnosis) and admitted to our Centre with non–ST–segment elevation myocardial infarction (NSTEMI) presentation were enrolled. Very high–risk NSTEMI patients had been excluded from the study. The prognostic value of an early (< 24 h) vs. deferred (≥ 24 h) coronary angiography was assessed. All–cause mortality and a composite endpoint (MACE) of all–cause mortality, stroke, re–hospitalization for heart failure and myocardial re–infarction were evaluated. Results: 198 NSTE–MINOCA patients were enrolled, of which 79 underwent coronary angiography < 24 hours and 119 ≥ 24 hours. MINOCA patients were more frequently females (64%) and the mean age was 66.8±13.2 years. After a median follow–up of 26 [14–40] months, the overall all–cause mortality was 13, 6% and the composite endpoint (MACE) was achieved in 27.3% of the entire population. Kaplan–Meier curves showed that there was no statistically significant difference (p = 0.88) between the two study groups depending on the time of invasive strategy adopted. Specifically, rates of death (11.4% vs. 15.1%) and MACE (25.3% vs. 28.6%) were similar in MINOCA patients undergoing early versus deferred coronary angiography. Conclusions: We demonstrated for the first time that in the MINOCA population the prognosis is not influenced by an early versus deferred coronary angiography, as opposed to AMI patients with obstructive coronary arteries. These results add another piece to the puzzle and pave the way for the initial use of a non–invasive imaging strategy (eg. Coronary–CT), mostly in patients with NSTEMI and high clinical suspicion of non–obstructive coronary arteries.